2007
DOI: 10.1111/j.1744-7348.2007.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition on disease development caused by fungal pathogens: implications for plant disease control

Abstract: A great deal of information is available in the literature on the effects of nutrition on disease development in plants and crops. However, much of this information is contradictory and although it is widely recognised that nutrition can influence disease in crops, limited progress has been made in the manipulation of crop nutrition to enhance disease control. Achieving this aim requires a sound understanding of the effects of fertilisation on nutrient levels and availability in crop tissues, and in turn, how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(209 citation statements)
references
References 131 publications
(189 reference statements)
6
192
1
10
Order By: Relevance
“…This result contrasted with similar comparisons in the literature; several have reported high concentrations of N in the canopy favored leaf rust (Walters and Bingham, 2007), powdery mildew (Olesen et al, 2003a), and septoria (Howard et al, 1994; Lovell et al, Table 10. UTC, untreated check no fungicide; T3, fungicide at Zadoks Growth Stage (GS) 65; T123, fungicide at approximately GS 30, GS 39, and GS 65.…”
Section: ---------------------------% Severity † --------------------contrasting
confidence: 56%
See 3 more Smart Citations
“…This result contrasted with similar comparisons in the literature; several have reported high concentrations of N in the canopy favored leaf rust (Walters and Bingham, 2007), powdery mildew (Olesen et al, 2003a), and septoria (Howard et al, 1994; Lovell et al, Table 10. UTC, untreated check no fungicide; T3, fungicide at Zadoks Growth Stage (GS) 65; T123, fungicide at approximately GS 30, GS 39, and GS 65.…”
Section: ---------------------------% Severity † --------------------contrasting
confidence: 56%
“…This was a synergistic response to high N and fungicide because the response was greater than the sum of responses for a high N rate (170 vs. 100) and inclusion of fungicides (no fungicide vs. three applications), or 0.48 and 0.67 Mg ha -1 , respectively. The synergism between N and fungicide has been reported in the literature, but the synergistic yield improvements have not been as great or consistent as those presented in this study, and most are reported from environments that traditionally practice intensive wheat management (Ruske et al, 2003a;Olesen et al 2000;Walters and Bingham, 2007;Delin et al 2008). In contrast, Olesen et al (2003b) reported yield increases with N rates and fungicide applications, but the study did not show any interaction between N application rate and fungicide.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…However, the molecular mechanisms underlying the central metabolic aspects of plant-pathogen interactions are poorly understood. Nitrogen (N) metabolism is a case in point now that available data for the role of N in disease appear rudimentary and even contradictory in most cases (Solomon et al, 2003;Walters and Bingham, 2007). The competition for a N source between the pathogen and its host is a dynamic and complex process.…”
Section: Introductionmentioning
confidence: 99%